La fábula, recurso didáctico eficaz para fortalecer la práctica de valores en el cuarto grado de Educación General Básica - Minga Guamán, Sisa Pacari (2025)
The Curriculum Integration Project: The Fable, an Effective Teaching Resource to Strengthen the Practice of Values in Fourth Grade of Basic General Education, aims to analyze the impact of the fable on strengthening the practice of values in the fourth-grade students of "Carlos Burneo Arias" School, during the 2024-2025 academic year. This is complemented by the following specific objectives: to diagnose the practice of values in the fourth-grade students of Basic General Education, to identify teaching strategies to strengthen the practice of values, and to design an alternative framework to strengthen the practice of values in fourth-grade students. It is a descriptive research study with a mixed-method approach and quasi-experimental design. The theoretical framework addresses topics related to fables and the practice of values. The research process employed the following methods: scientific, analytical, synthetic, descriptive, and statistical. Information was gathered through an interview with the teacher and a diagnostic evaluation of the students. The study population consisted of one teacher and fifteen students from the fourth-grade “A” class of "Carlos Burneo Arias" School. The results revealed the need to take actions to strengthen the practice of values. To this end, the alternative framework "Fables and Values: A Fantastic Journey Toward Personal Growth" was designed, with activities aimed at reinforcing the practice of values in the classroom, using the fable as the main tool. The conclusion is that the fable is an effective teaching resource for achieving this goal